Cellular phosphatidic acid sensor, α-synuclein N-terminal domain, detects endogenous phosphatidic acid in macrophagic phagosomes and neuronal growth cones - Haruka Yamada; Fumi Hoshino; Qiang Lu; Fumio Sakane (Biochemistry and Biophysics Reports, 2020)
Phosphatidic acid (PA) is the simplest phospholipid and is involved in the regulation of various cellular events. Recently, we developed a new PA sensor, the N-terminal region of α-synuclein (α-Syn-N). However, whether α-Syn-N can sense physiologically produced, endogenous PA remains unclear. We first established an inactive PA sensor (α-Syn-N-KQ) as a negative control by replacing all eleven lysine residues with glutamine residues. Using confocal microscopy, we next verified that α-Syn-N, but not α-Syn-N-KQ, detected PA in macrophagic phagosomes in which PA is known to be enriched, further indicating that α-Syn-N can be used as a reliable PA sensor in cells. Finally, because PA generated during neuronal differentiation is critical for neurite outgrowth, we investigated the subcellular distribution of PA using α-Syn-N. We found that α-Syn-N, but not α-Syn-N-KQ, accumulated at the peripheral regions (close to the plasma membrane) of neuronal growth cones. Experiments using a phospholipase D (PLD) inhibitor strongly suggested that PA in the peripheral regions of the growth cone was primarily produced by PLD. Our findings provide a reliable sensor of endogenous PA and novel insights into the distribution of PA during neuronal differentiation.